1992
DOI: 10.1073/pnas.89.1.222
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of aggregated native and mutant IgE receptors with the cellular skeleton.

Abstract: When aggregated, cell surface proteins become resistant to solubilization by detergents, presumably because of aggregation-induced or -stabilized interactions between the membrane protein and the cytoskeleton or plasma membrane skeleton. We genetically engineered variants of the tetrameric high-affinity receptor for IgE (Fc6RI) to identify a site on its a, (3, or y chains that mediates such putative interactions. Using flow cytofluorometry, we studied rat basophilic leukemia cells, transiently transfected COS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

1992
1992
2001
2001

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…element sueh as microfilamcnls may be responsible for movcmenl of receptors inlo patches ami caps 12O.2I|. However, such movement has recently been reported lo be associated wilh lhe interaction of reeeptors, and one of the components of the membrane skeleton rather than with the cytoskcleton [6,22]. It is possible that in our model, the critical signalling event initiating the increase of glomerular pcrmcabilily occurs during cross-linking and aggregation ofthe epitopes.…”
Section: Discussionmentioning
confidence: 84%
“…element sueh as microfilamcnls may be responsible for movcmenl of receptors inlo patches ami caps 12O.2I|. However, such movement has recently been reported lo be associated wilh lhe interaction of reeeptors, and one of the components of the membrane skeleton rather than with the cytoskcleton [6,22]. It is possible that in our model, the critical signalling event initiating the increase of glomerular pcrmcabilily occurs during cross-linking and aggregation ofthe epitopes.…”
Section: Discussionmentioning
confidence: 84%
“…The final concentrations were 10 mM CHAPS, 2 mM lipids, 0.5 mM Na3VO4, 5 mM Na4P207, 5 mM EDTA, and the same protein inhibitors as noted above. The samples were left on ice for a minimum of 30 min (10). The cell specimens and the first sonicate were centrifuged for 1 min at 14,000 x g at 40C and 0.5 ml of supernatant was withdrawn for analysis; for the centrifuged sonicate and subsequent membrane fractions, this centrifugation step was omitted.…”
Section: Methodsmentioning
confidence: 99%
“…The principal reagents used in these studies have been described (10 (GIBCO/BRL) and containing 32p (200-500 ,uCi/ml; 1 Ci = 37 GBq) before trypsin treatment.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is known that receptor aggregation results in an increased association of Fc⑀RI with membrane skeletal proteins (32), and it has been suggested that lipid-mediated interactions between Fc⑀RI and the plasma membrane occur before tyrosine phosphorylation (33). Evidence is accumulating that initiation of Fc⑀RI signaling depends on how Fc⑀RI and tyrosine kinase Lyn interact with cholesteroland sphingolipid-rich regions within the plasma membrane (34).…”
Section: Discussionmentioning
confidence: 99%